THE PERCEPTIONS OF SUGAR PALM FARMERS IN RELATION TO THE INSTITUTIONAL DEVELOPMENT OF SUGAR PALM AGRO-INDUSTRY - Pulungan, Sutan; Syahni, Rahmat; Nofialdi, Nofialdi; Nazir, Novizar (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This research was conducted in Tapsel Regency, North Sumatra for 8 months starting in April 2018, in 24 villages located in 4 sub-districts out of 14 sub-districts, determined by the Multistage Sampling Technique. Determination of respondents by purposive sampling technique. The respondents observed were 112 sugar palm farmers. Determination of respondents by purposive sampling technique. Research objectives: To describe the conditions and perceptions of sugar palm farmers in relation to the development of sugar palm agro-industry institutions. Data analysis techniques: Descriptive Analysis. Arranged variables; variable Y; Agroindustry Institutions, and variable X consists of 1. Human Resources, 2. Interaction, 3. Motivation, 4. Farmer Participation, and 5. Socio-Economic. Measured through 14 parameters spread over 49 lists of structured questions on the questionnaire. Farmers' responses to the questionnaire were assessed using a Likert Scale to identify and interpret the conditions and perceptions of sugar palm farmers. The results of the research produce recommendations: 1. Instilling confidence in sugar palm farmers, is important 2. Socialization is needed to sugar palm farmers, for example about; standard price of palm sugar, the technology used and the performance of the agro-industry. 3. The issue of agro-industry institutional leaders must go through a separate study.